Efficiency of qualitative mastering of rowing technique elements in 10-11 year old kayakers - Ikromov, B. F. (Mental Enlightenment Scientific-Methodological Journal, 2025)
The article reveals the effectiveness of the means and methods used to develop the stability of the balance of kayak rowers at the initial stage of training with the help of innovative simulators and special exercises.